Hydrogen retention in beryllium: concentration effect and nanocrystalline growth. (12th November 2015) - Pardanaud, C; Rusu, M I; Martin, C; Giacometti, G; Roubin, P; Ferro, Y; Allouche, A; Oberkofler, M; Köppen, M; Dittmar, T; Linsmeier, Ch
Abstract: We herein report on the formation of BeD2 nanocrystalline domes on the surface of a beryllium sample exposed to energetic deuterium ions. A polycrystalline beryllium sample was exposed to D ions at 2 keV/atom leading to laterally averaged deuterium areal densities up to 3.5 10 17 D cm −2, and studied using nuclear reaction analysis, Raman microscopy, atomic force microscopy, optical microscopy and quantum calculations. Incorporating D in beryllium generates a tensile stress that reaches a plateau at  ≈1.5 10 17 D cm −2 . For values higher than 2.0 10 17 cm −2, we observed the growth of  ≈90 nm high dendrites, covering up to 10% of the surface in some zones of the sample when the deuterium concentration was 3  ×  10 17 D cm −2 . These dendrites are composed of crystalline BeD2, as evidenced by Raman microscopy and quantum calculations. They are candidates to explain low temperature thermal desorption spectroscopy peaks observed when bombarding Be samples with D ions with fluencies higher than 1.2 10 17 D cm −2 .